2012
DOI: 10.1007/s10530-012-0355-1
|View full text |Cite
|
Sign up to set email alerts
|

Fire promotes downy brome (Bromus tectorum L.) seed dispersal

Abstract: Particularly well-known among the many impacts of the invasive annual grass downy brome (Bromus tectorum, Poaceae) is its ability to alter fire cycles and increase in abundance after fire. However, little is known about how fire influences B. tectorum dispersal. We quantified fire effects on B. tectorum dispersal using three recently burned areas in the western region of the Colorado Rocky Mountains by marking diaspores (seeds) with fluorescent powder, and then recovering them at night using ultraviolet lights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…In recent times however, opening through fire results also in an increased susceptibility of the burnt ecosystems towards the colonization of invasive alien species (Grund et al, 2005;Lonati et al, 2009;Maringer et al, 2012) or animal communities, e.g., Lyet et al (2009) and Blant et al (2010). Similar to what is reported for the Mediterranean (Arianoutsou and Vilà , 2012) or other fire prone ecosystems (Franklin, 2010;Monty et al, 2013), also in the Alpine environments fire may represent an unrequested spread channel for alien invasive species with pioneer character, what reinforce the selective pressure of fire in favour of disturbance adapted species of both native (Delarze et al, 1992;Tinner et al, 2000;Moser et al, 2010) and alien origin (Lonati et al, 2009;Maringer et al, 2012) (Fig. 7).…”
Section: Factors Limiting Fire Suppression Capacitysupporting
confidence: 66%
“…In recent times however, opening through fire results also in an increased susceptibility of the burnt ecosystems towards the colonization of invasive alien species (Grund et al, 2005;Lonati et al, 2009;Maringer et al, 2012) or animal communities, e.g., Lyet et al (2009) and Blant et al (2010). Similar to what is reported for the Mediterranean (Arianoutsou and Vilà , 2012) or other fire prone ecosystems (Franklin, 2010;Monty et al, 2013), also in the Alpine environments fire may represent an unrequested spread channel for alien invasive species with pioneer character, what reinforce the selective pressure of fire in favour of disturbance adapted species of both native (Delarze et al, 1992;Tinner et al, 2000;Moser et al, 2010) and alien origin (Lonati et al, 2009;Maringer et al, 2012) (Fig. 7).…”
Section: Factors Limiting Fire Suppression Capacitysupporting
confidence: 66%
“…In grasslands, where the vegetation cover is higher, seed entrapment strongly reduced average dispersal distances. These results confirm those of Johnston (2011) and Monty et al (Monty et al, 2013), who found even more important rates of secondary dispersal of B. tectorum in areas with almost no vegetation (reclamation and burned areas, respectively). Research on other species also found an influence of vegetation on ground level dispersal through a decrease in wind speed, changes in wind turbulence and seed entrapment (Chambers, 2000;Marushia and Holt, 2006;McEvoy and Cox, 1987).…”
Section: Dispersal Steps and Agents -supporting
confidence: 90%
“…The most distal florets are often sterile, and remain attached to the most distal fertile caryopsis after fruit set. This results in two types of diaspores (Monty et al, 2013): the simple ones, consisting of a single filled caryopsis with an awned lemma and the complex ones including one filled caryopsis and one or several sterile florets, resulting in a diaspore with two or more awns (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations